In vivo accumulation of cyclin A and cellular replication factors in autonomous parvovirus minute virus of mice-associated replication bodies - Bashir, Tarig; Rommelaere, Jean; Cziepluch, Celina (Journal of virology, 2001)
Autonomous parvovirus minute virus of mice (MVM) DNA replication is strictly dependent on cellular factors expressed during the S phase of the cell cycle. Here we report that MVM DNA replication proceeds in specific nuclear structures termed autonomous parvovirus-associated replication bodies, where components of the basic cellular replication machinery accumulate. The presence of DNA polymerases α and δ in these bodies suggests that MVM utilizes partially preformed cellular replication complexes for its replication. The recruitment of cyclin A points to a role for this cell cycle factor in MVM DNA replication beyond its involvement in activating the conversion of virion single-stranded DNA to the duplex replicative form.
Gesehen am 15.02.2021